(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The purpose of this paper is to analyze the hastened relationship between Erich Honecker and our country since he took position of the Embassy of Chile in Moscow in 1991. The so-called “Case Honecker” caused relevant fluctuations in our national politics and deep contradictions between our country’s legislative and executive duties, which tried to solve the international problem supposing a totally unexpected problem that occurred during the return to democracy in Chile. This paper has been made from the research elaborated in the General History Files of the Ministry of Foreign Affairs of Chile and the Library of the National Congress, mainly between 1991 and 1994. Also, we have researched in the national newspaper from those years. The documents reviews demonstrate the extents of this international process. The “Case Honecker”, thus, has became an important episode in the history of Foreign Affairs of Chile in the last decades